Characterization method for continuous fiber reinforced thermoplastic strands. (March 2021) - Domm, Matthias; Schlimbach, Jens; Mitschang, Peter
Due to increasing demand for flexibility and individualization, additive manufacturing (AM) is increasingly finding its way into industrial production processes. However, especially for the AM of polymers, the application possibilities are strongly limited by the achievable mechanical properties. One approach to overcome this disadvantage is the integration of reinforcing fibers. For easy handling and to decouple the time-consuming impregnation step from the AM process, it is advisable to use already impregnated semifinished products. Since the reliability of the AM process hardly depends on the quality of the semifinished products used, this study presents a quality analysis process for continuous fiber reinforced thermoplastic strands. The analysis procedure consists of 20 different quality criteria relating to geometry, fiber-matrix composite and mechanics. For easy comparability, the criteria can be calculated to a single quality index. The weighting of the criteria allows a simple transfer of the analysis process to various applications.